PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (STUDI KASUS PERUSAHAAN DAERAH AIR MINUM KABUPATEN REMBANG) - Suprapto, Edi; Nurhidayati, Anik (Universitas YPPI Rembang, 2022)
The Regional Drinking Water Company of Rembang Regency is a Regional Owned Enterprise that provides drinking water supply facilities in Rembang Regency. Maximum service to the community regarding the availability of drinking water must be balanced with maximum work completion efforts. Therefore, this study wanted to find out how the influence of leadership and compensation on employee performance with motivation as a moderating variable. The population is 109 employees, while the sample used is saturated sampling, because it uses all members of the population as samples. The data source uses primary data. Data collection techniques using a questionnaire. Data analysis using SEM (Structural Equation Modeling). The results of this study indicate that leadership has no significant positive effect on employee performance. Compensation has no significant negative effect on employee performance. Motivation has no significant negative effect on employee performance. Motivation moderates the influence of leadership on employee performance. Motivation does not moderate the effect of compensation on employee performance.Keywords: Leadership, Compensation, Motivation, Employee Performance